Malaria Transmission, Vector Diversity, and Insecticide Resistance at a Peri-Urban Site in the Forest Zone of Ghana - Akuamoah-Boateng, Yaw; Brenyah, Ruth C.; Kwarteng, Sandra A.; Obuam, Patrick; Owusu-Frimpong, Isaac; Agyapong, Addo K.; Badu, Kingsley (Frontiers in Tropical Diseases, 2021)
Introduction Recent surge of Anopheles resistance to major classes of World Health Organization (WHO)-approved insecticides globally necessitates the need for information about local malaria vector populations. It is believed that insecticide efficacy loss may lead to operational failure of control interventions and an increase in malaria infection transmission. We investigated the susceptibility levels of malaria vectors to all classes of WHO-approved vector control insecticides and described the dynamics of malaria transmission in a peri-urban setting. Methods Fit 3–5-day-old adults that emerged from Anopheles larvae collected from several different sites in the study area were subjected to the WHO bioassay for detecting insecticide resistance. The knockdown resistance gene (kdr) mutations within the vector populations were detected using PCR. Entomological inoculation rates were determined using the human landing catch technique and Plasmodium falciparum circumsporozoite ELISA. Results The malaria vectors from the study area were resistant to all classes of insecticides tested. Out of the 284 Anopheles complex specimen assayed for the resistance study, 265 (93.30%) were identified as Anopheles gambiae s.s. The kdr gene was detected in 90% of the Anopheles gambiae s.s. assayed. In an area where Anopheles coluzzii resistance to insecticides had never been reported, the kdr gene was detected in 78% of the Anopheles coluzzii sampled. The entomological inoculation rate (EIR) for the dry season was 1.44 ib/m/n, whereas the EIR for the rainy season was 2.69 ib/m/n. Conclusions This study provides information on the high parasite inoculation rate and insecticide resistance of malaria vectors in a peri-urban community, which is critical in the development of an insecticide resistance management program for the community.